Epipelic Diatom Community Structure in the Intertidal Zone Mengkapan Waters, Sungai Apit District, Siak Regency - Dionfriski, Adam; Siregar, Sofyan Husein; Nurrachmi, Irvina (Journal of Coastal and Ocean Sciences, 2021)
This research was conducted in December 2020 in Mengkapan Waters, Sungai Apit District, Siak Regency. The aims of this research was to analyze the composition, abundance, diversity index, uniformity index, and dominance index of epipelic diatom species in the intertidal zone. The method used is a survey method and the determination of the sampling location by purposive sampling based on anthropogenic activities around the waters. The water quality measured in this study were brightness, temperature, current velocity, salinity, pH, nitrate, and phosphate. Based on the research results, there are 19 species epipelic diatoms found in Mengkapan Waters, namely Coscinodiscus sp., Navicula sp., Gyrosigma sp., Thalassiosira sp., Pleurosigma sp., Synedra sp., Pinnularia sp., Surirella sp., Nitzchia sp., Triceratium sp., Melosira sp., Skeletonema sp., Stephanodiscus sp., Oscillatoria sp., Cocconeis sp., Epithemia sp., Diadesmis sp., Cymbella sp., and Amphipleura sp. The average value of abundance ranged from 29,245.37 – 35,744.33 ind/cm2, the diversity index value ranged from 2.5909 to 2.8014, the uniformity index value ranged from 0.6736 – 0.7755, and the dominance index ranged from 0.1684 - 0.2064. Based on one-way Anova test, concluded that abundance of epipelic diatoms between each stations weren’t significant.